2018
DOI: 10.1159/000493173
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Tamoxifen in the Prevention of Recurrent Urethral Strictures Following Internal Urethrotomy

Abstract: Objective: Tamoxifen was not used earlier in clinical practice to decrease the urethral re-stricture rate after visual internal urethrotomy (VIU). In this study, we are the first to report the use of Tamoxifen as an adjuvant therapy to decrease the re-fibrosis and stricture recurrence post-VIU. Patients and Methods: Between 2015 and 2017, 60 patients underwent VIU for post-traumatic bulbar urethral stricture ≤1 cm. They were randomly divided into 2 groups (30 patients each). The Tamoxifen group cases received … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Most studies in the current analysis did not report any significant adjunct-specific complications. Tamoxifen resulted in two (6.7%) patients having mild gynaecomastia (34). Although no significant side effects were reported with mitomycin C in this study, one retrospective study reported two cases of osteitis pubis and one case of rectourethral fistula when injecting mitomycin at the bladder neck for recalcitrant bladder neck stenosis (60).…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Most studies in the current analysis did not report any significant adjunct-specific complications. Tamoxifen resulted in two (6.7%) patients having mild gynaecomastia (34). Although no significant side effects were reported with mitomycin C in this study, one retrospective study reported two cases of osteitis pubis and one case of rectourethral fistula when injecting mitomycin at the bladder neck for recalcitrant bladder neck stenosis (60).…”
Section: Discussionmentioning
confidence: 55%
“…Only mitomycin C and local steroids have been studied in more than one RCT. Intraurethral instillation with hyaluronic acid and carboxymethylcellulose (26), PRP (31) and oral tamoxifen (34) have each been studied in single RCTs and the other adjuncts such as brachytherapy (28), captopril (30), paclitaxel-coated balloons (32,33) and oral deflazacort (35) have been evaluated in prospective or retrospective cohort studies.…”
Section: Discussionmentioning
confidence: 99%
“…Its anti-fibrotic activity has confirmed in several studies. El-Shazly et al showed that tamoxifen effectively prevents the recurrence of urethral stricture after internal urethrotomy and improvement of Qmax and IPSS score compared with the control group [18].In the rat model of Peyronie's disease, Ilg MM, et al demonstrated that the combination of vardenafil and tamoxifen inhibited the myofibroblast transformation and ECM production [19].…”
Section: Tamoxifenmentioning
confidence: 99%
“… 74 75 76 Moreover, TAM has been reported to reduce urethral stricture recurrence after visual IU. 77 …”
Section: Therapeutic Drugsmentioning
confidence: 99%